2014
DOI: 10.1002/sca.21176
|View full text |Cite
|
Sign up to set email alerts
|

Scanning and transmission electron microscopic analysis of ampullary segment of oviduct during estrous cycle in caprines

Abstract: The ampullary segment of the mammalian oviduct provides suitable milieu for fertilization and development of zygote before implantation into uterus. It is, therefore, in the present study, the cyclic changes in the morphology of ampullary segment of goat oviduct were studied during follicular and luteal phases using scanning and transmission electron microscopy techniques. Topographical analysis revealed the presence of uniformly ciliated ampullary epithelia, concealing apical processes of non-ciliated cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…We found that, after 4R and 8R, the tunicae mucosa and muscularis of mouse FTs appeared well-preserved by LM with no evident signs of morphological alterations, as in other mammals [ 45 , 46 ]. The ultrastructural analysis of CECs by TEM showed, in all groups, the presence of well-preserved nuclei and cell junctions, lipid droplets, ER tubules/networks, Golgi apparatuses, secondary lysosomes, multivesicular bodies and microvilli, in accordance with the literature describing the physiological morphology of oviducts [ 23 , 24 , 27 ]. However, electron microscopy evidenced specific changes affecting mitochondria and cilia of the CECs of the mucosa layer, especially after 8R.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found that, after 4R and 8R, the tunicae mucosa and muscularis of mouse FTs appeared well-preserved by LM with no evident signs of morphological alterations, as in other mammals [ 45 , 46 ]. The ultrastructural analysis of CECs by TEM showed, in all groups, the presence of well-preserved nuclei and cell junctions, lipid droplets, ER tubules/networks, Golgi apparatuses, secondary lysosomes, multivesicular bodies and microvilli, in accordance with the literature describing the physiological morphology of oviducts [ 23 , 24 , 27 ]. However, electron microscopy evidenced specific changes affecting mitochondria and cilia of the CECs of the mucosa layer, especially after 8R.…”
Section: Discussionsupporting
confidence: 88%
“…All the experimental procedures and the animals were maintained in accordance with national and international law and policies (European Economic Community Council Directive 86/609, OJ 358, 1 Dec 12, 1987; Italian Legislative Decree 116/92, Gazzetta Ufficiale della Repubblica Italiana n. 40, Feb 18, 1992; National Institutes of Health Guide for the Care and Use of Laboratory Animals, NIH publication no. 85- 23,1985). The Italian Ministry of Health and the local committee (University of L'Aquila) for the animal care and use approved the experimental protocols, in compliance with the accepted veterinary medical practice.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The folds are longitudinally different, forming secondaryto -tertiary folds, forming irregular net-like structures forming different troughs, vesicles and crypts (Yaniz et al, 2000;Kenngott and Sinowatz, 2007). Sharma et al (2015) describes characteristic pattern of variations in the ampullary segment of the uterine tube during follicular and luteal phases of estrous cycle in goat. The tunica mucosa of ampulla was characterized by presence of longitudinal mucosal folds throughout the length with extensive secondary and tertiary branches in follicular phase, whereas the luteal phase was characterized by primary and secondary branching patterns.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Previous research suggested a correlation between survival of ampullary cancer patients and expressions of membrane receptors for bile acids [9]. Genetic polymorphisms of lipid metabolism-related genes were correlated with the development of biliary tract cancer and ampullary cancer [10,11]. The mechanism of development of ampullary cancer remains inexplicit, and comprehensive analyses are required.…”
Section: Ivyspringmentioning
confidence: 99%